New lexical materials for the Proto-Afro-Asiatic anatomical and physiological terminology I: Body part names with initial labials: General terms, head and neck - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper constitutes the first part of a long-range series of studies gradually elaborating the enormous new materials of the anestral anatomical-physiological vocabulary of Proto-Afro-Asiatic, supposed to be the earliest known parental language spoken by the earliest known neolithic community on earth. This series is parallel to the author’s ongoing projects for a comprehensive analysis of the diverse segments of the immense new cultural lexicon that has emerged in course of the author’s root research over the past some three decades.